Statistical analyses and correlation between tropospheric temperature and humidity at Dome C, Antarctica. Issue 3 (19th September 2013) - Ricaud, P.; Carminati, F.; Courcoux, Y.; Pellegrini, A.; Attié, J.-L.; El Amraoui, L.; Abida, R.; Genthon, C.; August, T.; Warner, J.
Abstract The Dome C (Concordia) station in Antarctica (75°06′S, 123°21′E, 3233 m above mean sea level) has a unique opportunity to test the quality of remote-sensing measurements and meteorological analyses because it is situated well inside the Eastern Antarctic Plateau and is less affected by local phenomena. Measurements of tropospheric temperature and water vapour (H2O) together with the integrated water vapour (IWV) performed in 2010 are statistically analysed to assess their quality and to study the yearly correlation between temperature and H2O over the entire troposphere. The statistical tools include yearly evolution, seasonally-averaged mean and bias, standard deviation and linear Pearson correlation. The datasets are made of measurements from the ground-based microwave radiometer H2O Antarctica Microwave Stratospheric and Tropospheric Radiometer (HAMSTRAD), radiosonde, in situ sensors, the space-borne infrared sensors Infrared Atmospheric Sounding Interferometer (IASI) on the MetOp-A platform and the Atmospheric InfraRed Sounder (AIRS) on the Aqua platform, and the analyses from the European Centre for Medium-Range Weather Forecast (ECMWF). Despite some obvious biases within all these datasets, our study shows that temperature and IWV are generally measured with high quality whilst H2O measurement quality is slightly worse. The AIRS and IASI measurements do not have the vertical resolution to correctly probe the lowermost troposphere, whilst HAMSTRAD loses sensitivity in the upper troposphere-lower stratosphere. Within the entire troposphere over the whole year, it is found that the time evolution of temperature and H2O is highly correlated (> 0.8). This suggests that, in addition to the variability of solar radiation producing an obvious diurnal cycle in the planetary boundary layer in summer and an obvious seasonal cycle over the year, the H2O and temperature intra-seasonal variabilities are affected by the same processes, e.g. related to the long-range transport of air masses.